Evaluating the Effectiveness of Spreadsheet-Based Instruction on High School Students’ Data Literacy: A Pre-test–Post-test Study - Tubagus Robbi Megantara; Rizki Hidayana; Nenden Siti Nurkholipah; Rika Amelia; Abdul Gazir Syarifudin (International Journal of Research in Community Services, 2026)
Data literacy has become an essential competency for students in the digital era, particularly at the secondary education level where foundational numeracy skills are developed. Spreadsheet software such as Microsoft Excel offers an accessible platform for integrating mathematical concepts with practical data analysis and visualization. This study aims to quantitatively evaluate the effectiveness of a spreadsheet-based instructional intervention in improving high school students’ data literacy skills. A quasi-experimental one-group pre-test–post-test design was employed involving 12 senior high school students from SMAS Sebelas Maret, Bandung. The instructional intervention consisted of three integrated modules: Introduction to Excel and Data Literacy, Data Analysis and Logical Functions, and Data Visualization. Students’ competencies were assessed before and after the intervention using a structured test aligned with these modules. Data were analyzed using descriptive statistics, paired-sample t-tests, and effect size estimation (Cohen’s d). The results indicate a statistically significant improvement in overall performance from pre-test to post-test (p < 0.05), accompanied by a large effect size (d = -0.96), demonstrating substantial practical impact. The strongest learning gains were observed in data visualization skills, while data analysis and logical functions showed more moderate improvement. These findings suggest that spreadsheet-based instruction is an effective approach for enhancing data literacy and applied numeracy skills among high school students.